(3NHGjG GdRhGjG ajeG aj GdQLGd ef GdHbGjGs - (3CMeO Hf eMeO Hf YeQ, TgGH GdOjf GdNaGLj GdeUQj , GdTgGH GdNaGLj,J (B1069 (3g` s
(3ChdgG (B:s
(3Ghdg GdMeO ddg Gdge jWhb LjO GdHdGZI fXje YbhOg s
(3QJHg GdeDda Ydi NeSI CbSGe hfbdJ Yf fSNI GdeDda ai MjGJg SfI (B1042s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B238 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B138s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B285 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B12 s
Keywords: (3GdJGQjNs